The prevalence, characteristics and morbidity of neuropathic pain in AIDS patients, prior to the use of HAART, at the Kalafong Hospital HIV clinic, Pretoria - Hitchcock, Sonia Anne (Department of Public Health and Family Medicine, 2015)
Includes bibliographical references (leaves 49-56).